2020
DOI: 10.15567/mljekarstvo.2021.0104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plant extracts on antioxidant potential, microbial and sensory attributes of stirred yoghurt

Abstract: The aim of this study was to use various plants to increase the functional properties of yoghurt. The ethanol extracts of three different plant (Mentha piperita L., Ocimum basilicum L., and Hibiscus sabdariffa L.) extracts were added to the stirred type yoghurts at different ratios (0.1 %, 0.3 % and 0.5 %). The pH values, colour values, antioxidant activity, microbial and sensory attributes of yoghurt were evaluated on the storage days of 0, 7, 14, 21, and 28. The lowest pH values were found at the beginning (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Although instrumental measurement clearly resulted in large colour distinctions between OLE-enriched samples and the control sample ( Table 2 and Figure 4 ), sensory evaluation was not that precise, and the panel noticed colour changes only for sample OLE 5% ( Table 4 ). Such results corresponded to some previously published findings such as those of Dönmez et al [ 33 ] and Tomar et al [ 45 ], who detected considerable colour changes in yoghurt supplemented with green tea and coffee powder [ 33 ] or with mint, basil, or hibiscus extract [ 45 ], respectively. Cho et al [ 8 ] Tavakoli et al [ 22 ] also found that OLE addition negatively influenced colour, which was bright green, and the taste of yoghurt was often described as bitter and astringent.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Although instrumental measurement clearly resulted in large colour distinctions between OLE-enriched samples and the control sample ( Table 2 and Figure 4 ), sensory evaluation was not that precise, and the panel noticed colour changes only for sample OLE 5% ( Table 4 ). Such results corresponded to some previously published findings such as those of Dönmez et al [ 33 ] and Tomar et al [ 45 ], who detected considerable colour changes in yoghurt supplemented with green tea and coffee powder [ 33 ] or with mint, basil, or hibiscus extract [ 45 ], respectively. Cho et al [ 8 ] Tavakoli et al [ 22 ] also found that OLE addition negatively influenced colour, which was bright green, and the taste of yoghurt was often described as bitter and astringent.…”
Section: Resultssupporting
confidence: 92%
“…It could be observed that the added plant extracts (OLE) significantly ( p < 0.001) enhanced the antioxidant activity of yoghurt, especially at higher concentrations (OLE 3% and OLE 5%), which was similar to findings of some recent studies. Tomar et al [ 45 ] examined the addition of various plant extracts (mint, basil, hibiscus) in concentrations ( v / v ) of 0.1%, 0.3%, and 0.5% to cow milk yoghurt and also found a linear increase in antioxidant activity measured by the DPPH method. Based on their findings, the activities for the control sample were almost identical (10–20% radical scavenging power) to the results in this study ( Figure 3 b).…”
Section: Resultsmentioning
confidence: 99%
“…It is widely used because of its bioactive properties in fighting bacterial diseases, anti-inflammatory and immune modulatory agents [8] .The effects of yoghurt fortification with rhubarb , grape seed, thyme, green tea and mint on physicochemical , rheological, textural and sensory properties during cold storage had been reported [9] . Similarly, the effect of plant extracts on antioxidant potential, microbial and sensory attributes of stirred yoghurt [10] and fortification of yoghurt with thyme and grape seed extracts [11] had been reported. Based on limited information on the food an application of extracts from C. citrates, C. papaya, S. bicolour and O. gratisimum, this research aims at determining their effect on the phytochemical, antioxidant, physiochemical and sensory properties of yoghurt.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the number of dairy products in the market has increased in the past decade, with a wide variety of products relative to flavored yogurt. Furthermore, the addition of traditional herbs and/or vegetable foods or extracts allows the preparation of yogurt with enhanced healthy properties thanks to the presence of phenolic compounds [ 3 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%